Participatory Learning Management in Improving Students' English Subject Skills - Noerlina Anggraeni; Ulfiah; Deti Rostini; Rita Sulastini (Yayasan Azka Hafidz Maulana, 2022)
The problems faced in the school management system which is functionally not running optimally, where the supporting factors for activities, especially financing, are the lack of transparency. Moreover, the administration of job is not given based on proportional and professional principles; it is more inclined to the principle of closeness and seniority. In addition, team work is also less solid and less intelligent in responding to various school problems, especially in learning outcomes. Network has not described the relationship between effective and productive work procedures. In particular, the difficulties encountered include: (a) Media and learning facilities that are not on target, (b) Education funding has not been in accordance with the needs, (c) The competence of educators is not evenly distributed, (d) Teacher welfare needs to be improved, (e) The different psychological development of students, (f) The monitoring system has not been maximized. In addition, the teacher's ability to understand the characteristics of students is weak, the use of learning methods is not appropriate, the vision and mission and goals are not fully understood by the teachers, the mentality and awareness of teachers are weak to improve their competence, the results of the guidance of the principal and supervisors are rarely followed up, low community participation. The school management system is still central and closed. The purpose of this study was to obtain an overview of the management of Participatory Learning Management in Improving the Ability of Students in English Subjects at SMAN 89 and SMAN 102 DKI Jakarta Province. The research method used in this study is a descriptive method with a qualitative approach; this method is used to solve the problem under study where this research is intended to explore data and information related to Participatory Learning Management in Improving Students' English Subject Skills at SMAN DKI Jakarta. At the planning stage of learning English in improving English for high school students in Jakarta, it has been stated in the syllabus. The stage of organizing that has been carried out is good, but improvements are still needed in its implementation. In the implementation stage of participatory learning in improving entrepreneurial behavior in high school in Jakarta, English teachers have carried out the learning process with steps of normative learning activities according to the syllabus and lesson plans including very good qualifications. The evaluation activity stage is carried out in the assessment of participatory learning in improving students' English at high school in Jakarta, in the assessment stage the English Skills Education teacher conducts two types of assessments, namely process assessment and student learning outcomes assessment. Learning English at the planning stage still lacks good learning strategies and supportive learning media. To increase student participation in English, it is necessary to have a comprehensive approach to students, interesting learning media.